ANALISIS TERHADAP TIGA PASANGAN MUDA DALAM PRIDE AND PREJUDICE KARYA JANE AUSTEN DARI PERSPEKTIF PSIKOANALISIS - Asmarani, Ratna (HUMANIKA, 2013)
ABSTRACT The purpose of this paper is to analyze the three young couples in Jane Austen’s novel entitled Pride and Prejudice. The approach used in this paper is Freud’s psychoanalysis focussing on the three personality components, namely id, ego, and superego in order to dig out the psychological characters of each couple. The results of the analysis show that every couple tends to have similar psychological characters and the colour of their marriage life is influenced by the psychological characters of each couple. Keywords: psychoanalysis, id, ego, superego, psychological characters